Ustrój sądów karnych i wojskowych organów dyscyplinarnych w Wielkopolsce w okresie Powstania Wielkopolskiego 1918/1919. - Bojarski, Adam (My University, 2020)
W trakcie Powstania Wielkopolskiego 1918/1919 sądownictwo było podzielone pomiędzy sądy doraźne, sądy wojskowe, sądy wojskowe dla formacji Wielkopolskich w polu oraz sądy polowe. Natomiast wojskowe organy dyscyplinarne dzieliły się na: głównodowodzącego, dowódców jednostek wojskowych lub jednostek frontowych, dowódców urzędów wojskowych oraz Sądy Straży Ludowej. Głównym celem rozprawy jest omówienie prawnych założeń działalności utworzonego sądownictwa oraz wojskowych organów dyscyplinarnych od momentu wybuchu Powstania Wielkopolskiego 1918/1919 do momentu przejęcia wymiaru sprawiedliwości przez Rzeczpospolitą Polską, które miało miejsce w dniu 1 stycznia 1920 roku.

During the Greater Poland Uprising 1918/1919 the judiciary was divided between summary courts, military courts, military courts for field formations of Greater Poland and field courts. Whereas military disciplinary authorities were divided into: Commander-in-Chief, commanders of military units or frontal units, commanders of military offices and People's Guard Courts. The main aim of the trial is to discuss the legal assumptions of the activities of the established judiciary and military disciplinary authorities from the outbreak of the Greater Poland Uprising 1918/1919 until the takeover of justice by the Republic of Poland, which took place on 1 January 1920.
The system of criminal courts and military disciplinary authorities in Great Poland during the Greater Poland Uprising 1918/1919.
Wydział Prawa i Administracji
Keywords: sąd doraźny; sąd wojskowy; wojskowy organ dyscyplinarny; sąd polowy; Powstanie Wielkopolskie 1918/1919; summary court; military court; military disciplinary authorities; field court; Greater Poland Uprising 1918/1919